Definisi Ahl al-Sunnah wa Al-JamaAh: Satu Analisis - Engku Alwi, Engku Ahmad Zaki (Jurnal Usuluddin, 2007)
Ahl al-Sunnah wa al-Jamaah has been practiced by Muslim society since a long time ago in their ways of life especially in theology. Nonetheless, Muslim society are still misunderstanding the facts of Ahl al-Sunnah wa al-Jamaah. This article attempts to analyse the definition of Ahl al-Sunnah wa al-Jamaah and its development in Islamic theology. Several issues regarding Ahl al-Sunnah wa al-Jama`ah are also briefly discussed.